Main characteristics of 11th -15th centuries bricks from monumental buildings of the Pechersk monastery in Kyiv - Olena Olehivna Makhota (Slavia Antiqua, 2023)
The relevance of the proposed work lies in the fact that the powerful collection of building materials has been assembled in the scientific funds of the National Preserve „Kyiv-Pechersk Lavra” over a 100-year history of archaeological research into architectural monuments from the 11th-15thcenturies (the Dormition Cathedral, chapel of St. John the Baptist, Trinity Gatech church, a brick refectory, and a stonewall from the 12thcentury). It consists of bricks (plinthois), ceramic tiles and stone floor slabs, roof tiles, glass hutters, frescoes, mosaics, samples of stones and solutions, marble decorative elements, etc. Among the most massive and informative materials is a plinthoi. The study of its characteristics and historical and cultural significance is aimed at acquiring a body of knowledge about building materials. M. Kholostenko, G. Ivakin, O. Syromyatnikov, and D. Jolshin were engaged in the study of bricks from the Pechersk monastery. However, no generalizing work on construction materials of the 11th-15th centuries of these monuments of ancient Kyiv has been carried out till now.